KOMPETENSI PROFESIONAL GURU YANG BERSERTIFIKASI DAPAT MENINGKATKAN PRESTASI BELAJAR SISWA - Endang Pristiawaty (Universitas Negeri Medan, 2014)
Essential competencies professorship is professional competence, social competence, and personal competence. Professional competency, competence in the field of substance or field of study, competence areas of learning, teaching methods, assessment systems, the value of education and guidance. Social competence, competence in the field of relationship and service, community service. Personal competence, competence value built through behaviors that teachers, has a personal and attractive appearance, impressive and teachers slang and